QUEST-RA: quantitative clinical assessment of patients with rheumatoid arthritis seen in standard rheumatology care in 15 countries. - Sokka, T; Kautiainen, H; Toloza, S; Mäkinen, H; Verstappen, S; Lund Hetland, M; Naranjo, A; Baecklund, E; Herborn, G; Rau, R; Cazzato, M; Gossec, L; et al. (2007)
OBJECTIVE: To conduct a cross-sectional review of non-selected consecutive outpatients with rheumatoid arthritis (RA) as part of standard clinical care in 15 countries for an overview of the characteristics of patients with RA. METHODS: The review included current disease activity using data from clinical assessment and a patient self-report questionnaire, which was translated into each language. Data on demographic, disease and treatment-related variables were collected and analysed using descriptive statistics. Variation in disease activity on DAS28 (disease activity score on 28-joint count) within and between countries was graphically analysed. A median regression model was applied to analyse differences in disease activity between countries. RESULTS: Between January 2005 and October 2006, the QUEST-RA (Quantitative Patient Questionnaires in Standard Monitoring of Patients with Rheumatoid Arthritis) project included 4363 patients from 48 sites in 15 countries; 78% were female, >90% Caucasian, mean age was 57 years and mean disease duration was 11.5 years. More than 80% of patients had been treated with methotrexate in all but three countries. Overall, patients had an active disease with a median DAS28 of 4.0, with a significant variation between countries (p<0.001). Among 42 sites with >50 patients included, low disease activity of DAS28 <or=3.2 countries,="" countries;="" eight="" five="" found="" in="" majority="" of="" other="" patients="" seven="" sites="" the="" was="">50% of patients had high disease activity of DAS28 >5.1. CONCLUSIONS: This international multicentre cross-sectional database provides an overview of clinical status and treatments of patients with RA in standard clinical care in 2005-6 including countries that are infrequently involved in clinical research projects.</or=3.2>